A Distributed Resource Allocation Algorithm for the General Linear Multiagent Systems. (22nd August 2022) - Li, M.; Shao, B.; Shi, X.
Abstract : We study the distributed resource allocation problem for heterogeneous multiagent systems over an undirected graph, an essential issue in multiagent system coordinated control and complex network system control. The decision variable is subject to global equality and local convex set constraints, and the objective is smooth and convex. It aims to minimize the global objective function by exchanging neighboring information between agents. An adaptive distributed algorithm is designed using the distance function-based exact penalty function method. A state- and time-based triggering condition is designed to avoid continuous communication and reduce the communication burden. From a random initial state, the proposed algorithm asymptotically converges to the optimal value by means of LaSalle's invariance principle. Finally, examples are provided to demonstrate the effectiveness of our algorithm.